Transcriptome analysis of Artemisia argyi following methyl jasmonate (MeJA) treatment and the mining of genes related to the stress resistance pathway - Wang, Jing; Cui, Yupeng; Li, Shuyan; Gao, Xinqiang; Zhang, Kunpeng; Shen, Xiangling (Frontiers in Genetics, 2023)
The experimental material Artemisia argyi was utilized in this study to investigate the treatment of A. argyi with exogenous MeJA at concentrations of 100 μmol/L and 200 μmol/L for durations of 9 h and 24 h respectively. Transcriptome sequencing was conducted using the Illumina HiSeq platform to identify stress resistance-related candidate genes. Finally, a total of 102.43 Gb of data were obtained and 162,272 unigenes were identified. Differential analysis before and after MeJA treatment resulted in the screening of 20,776 differentially expressed genes. The GO classification revealed that the annotated unigenes were categorized into three distinct groups: cellular component, molecular function, and biological process. Notably, binding, metabolic process, and cellular process emerged as the most prevalent categories among them. The results of KEGG pathway statistical analysis revealed that plant hormone signal transduction, MAPK signaling pathway-plant, and plant-pathogen interaction were significant transduction pathways in A. argyi' s response to exogenous MeJAinduced abiotic stress. With the alteration of exogenous MeJA concentration and duration, a significant up-regulation was observed in the expression levels of calmodulin CaM4 (ID: EVM0136224) involved in MAPK signaling pathway-plant and auxin response factor ARF (ID: EVM0055178) associated with plant-pathogen interaction. The findings of this study establish a solid theoretical foundation for the future development of highly resistant varieties of A. argyi.